Narasi Gempa dalam Otobiografi Moehammad Saleh Datoek Rangkayo Basa - Undri, Mr - (Masyarakat Sejarawan Indonesia, 2019)
This paper attempst to explain the account of earthquake within autobiography of Moehammad Saleh Datoek Rangkayo Basa. He was a captain and merchant from Minangkabau who wrote his autobiography when he turned 73 in 1914. The story of his original life was handwritten in Minangkabau language using Arabic-Malay letters (or bald Arabic letters) of Minangkabau (Pariaman) coastal dialect. In the 1920s, his grandson, Soetan Mahmoed (S.M) Latif began copying the manuscript into Latin letters in the form of stencils. The literacy work (transliteration) could only be completed in 1933 and printed in limited numbers in Bandung in 1933, 1965 and 1975 to be distributed to members of Moehammad Saleh family. From the biography, it is obtained an overview of the events of the earthquake that occurred, especially on Telo Island and its surroundings. When the earthquake struck, all residents jumped out of their homes. The earthquake shaking was very hard and lasted a little longer, orced the locals to flee into the hill. People got panic and in a matter of minutes suddenly sea water rose suddenly. The land near the port was submerged in water and houses and markets were overunned by water. The tsunami did not hit Telo Island, but the area on Simuk Island and even on the western side of the island were invaded by tsunami and in aftermath,, corpses scattered amidst coconut trunks and lying everywhere.